The Conley-Zehnder indices of the rotating Kepler problem - Albers, Peter (Mathematical proceedings of the Cambridge Philosophical Society, 2013)
We determine the Conley-Zehnder indices of all periodic orbits of the rotating Kepler problem for energies below the critical Jacobi energy. Consequently, we show the universal cover of the bounded component of the regularized energy hypersurface is dynamically convex. Moreover, in the universal cover there is always precisely one periodic orbit with Conley-Zehnder index 3, namely the lift of the doubly covered retrograde circular orbit.
First published online 3 October 2012
Gesehen am 18.02.2019